Pembatalan Order dalam Aplikasi Indriver untuk Menghindari PPN dan Komisi Perspektif Imam An-Nawawi - Albaraday, Ahmad; Hidayat, Rahmat (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2025)
This study aims to examine the practice of order cancellation by drivers on the InDriver application as a strategy to avoid VAT and commission deductions, viewed from the perspective of Islamic transaction ethics according to Imam An-Nawawi. This study uses empirical juridical research with data collection techniques through in-depth interviews and observations, as well as a purposive sampling approach to active drivers who use the InDriver application in Medan and its surroundings. The results show that the practice of canceling orders with an agreement between the driver and passenger to continue the trip outside the application system is done consciously as a form of tax and commission deduction avoidance. Informants stated that this action is done for economic reasons, limited balance, and the influence of the social environment of fellow drivers. Although it is acknowledged that this practice is not entirely ethical and contains elements of manipulation, it is still considered reasonable under certain conditions. From Imam An-Nawawi's perspective, honesty is a key principle in transactions. Actions to avoid established obligations, such as commissions or VAT, fall into the category of fraud and contradict Islamic values. Therefore, the practice of intentionally canceling orders is considered inconsistent with Sharia principles that uphold trustworthiness, justice, and blessings in seeking sustenance. This study recommends the need for ongoing Islamic business ethics education for online transportation operators, as well as more prudent government policies in setting VAT and commission rates that align with the socioeconomic conditions of the community, particularly for online motorcycle taxi drivers.